New york to dallas ebook - Robb, J. D. (In Death, 2011)
#1 New York Times bestselling author J. D. Robb presents an intense and terrifying case for New York homicide cop Eve Dallas: one that will take her all the way to the city that named her—and plunge her into the nightmares of her childhood... When a monster named Isaac McQueen—taken down by Eve back in her uniform days—escapes from Rikers, he has two things in mind. One is to take up where he left off, abducting young victims and leaving them scarred in both mind and body. The other is to get revenge on the woman who stopped him all those years ago.